Analisis produk tanaman pangan dan hortikultura serta strategi pengembangannya di Kabupaten Kerinci - Fetra, Riza; Erfit, Erfit; Zamzami, Zamzami (Jurnal Paradigma Ekonomika, 2021)
The data used is secondary data in the 2015-2019 period. The data analysis method uses Location Quotient (LQ) analysis, Dynamic Location Question (DLQ), and SWOT analysis. The purpose of this study is to determine whether the commodity understudy is included in the base sector or non-base sector by using Location Quotient (LQ) analysis, Dynamic Location Question (DLQ), and its development strategy in Kerinci Regency using SWOT analysis. It was found that the commodities of shallots, chilies, potatoes, cabbage, Chinese cabbage, sweet potatoes, and tomatoes were included in the base commodities using the LQ method. In contrast, with the DLQ method, all the commodities studied would be the basis in the future. Â